2023
DOI: 10.11646/zootaxa.5228.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative approach reveals the identity of Brazilian specimens previously recognized as Anastrepha dissimilis Stone, 1942 (Diptera: Tephritidae)

Abstract: Anastrepha dissimilis is currently considered to be widely distributed in Brazil, occurring in 20 of 27 states. However, morphological differences between the holotype (from Plaisance, Haiti) and a paratype (from Pernambuco, Brazil) suggest that the Brazilian specimens are not A. dissimilis, because their aculeus tip is similar to the paratype not to the holotype. Therefore, considering the importance of integrative taxonomy for species delimitation, we used geometric and linear morphometrics and cytochrome c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The occurrence of Anastrepha chiclayae Greene in guava fruits in Brazil was verified for the first time in this study. Anastrepha chiclayae had its identity recently clarified in Brazil: morphological, morphometric and molecular studies (integrative analysis) have shown that specimens previously misidentified as A. dissimilis in Brazil are A. chiclayae (Araújo et al 2023). This species is distributed in all the Brazilian geographic regions, with plant hosts including Passiflora caerulea L., Passiflora edulis Sims and Passiflora elegans Mart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of Anastrepha chiclayae Greene in guava fruits in Brazil was verified for the first time in this study. Anastrepha chiclayae had its identity recently clarified in Brazil: morphological, morphometric and molecular studies (integrative analysis) have shown that specimens previously misidentified as A. dissimilis in Brazil are A. chiclayae (Araújo et al 2023). This species is distributed in all the Brazilian geographic regions, with plant hosts including Passiflora caerulea L., Passiflora edulis Sims and Passiflora elegans Mart.…”
Section: Resultsmentioning
confidence: 99%
“…(Sapotaceae) and Sarcomphalus joazeiro (Mart.) Hauenschild (Rhamnaceae) (Zucchi & Moraes 2022a, Araújo et al 2023). Anastrepha dissimilis is not known to occur in Brazil (Araújo et al 2023).…”
Section: Resultsmentioning
confidence: 99%